Comparison of posture among adolescent male volleyball players and non-athletes - Grabara, Małgorzata (Biology of Sport, 2015)
Due to high training loads and frequently repeated unilateral exercises, several types of sports training can have an impact on the process of posture development in young athletes. The objective of the study was to assess and compare the postures of adolescent male volleyball players and their non-training peers. The study group comprised 104 volleyball players while the control group consisted of 114 non-training individuals aged 14-16 years. Body posture was assessed by the Moiré method. The volleyball players were significantly taller, and had greater body weight and fat-free mass. The analysis of posture relative to symmetry in the frontal and transverse planes did not show any significant differences between the volleyball players and non-athletes. Postural asymmetries were observed in both the volleyball players and the control participants. Lumbar lordosis was significantly less defined in the volleyball players compared to non-training individuals while no difference was observed in thoracic kyphosis. All athletes demonstrated a loss of lumbar lordosis and an increase in thoracic kyphosis. Significant differences in anteroposterior curvature of the spine between the volleyball players and the non-athletes might be associated with both training and body height. Considering the asymmetric spine overloads which frequently occur in sports training, meticulous posture assessment in young athletes seems well justified.